2015
DOI: 10.1097/dss.0000000000000486
|View full text |Cite
|
Sign up to set email alerts
|

Avoiding and Treating Blindness From Fillers

Abstract: Although the risk of blindness from fillers is rare, it is critical for injecting physicians to have a firm knowledge of the vascular anatomy and to understand key prevention and management strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
230
0
6

Year Published

2015
2015
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 420 publications
(238 citation statements)
references
References 43 publications
2
230
0
6
Order By: Relevance
“…Plastic surgeons nowadays are working on improved injection techniques and rescue solutions once embolism occurred. [33][34][35] Our injected 3D MA-HA cryogel had a diameter of 5 mm, which is far larger than the diameter of subcutaneous blood vessels, thus minimizing the risk of inadvertent blood vessel embolization.…”
Section: 27mentioning
confidence: 99%
“…Plastic surgeons nowadays are working on improved injection techniques and rescue solutions once embolism occurred. [33][34][35] Our injected 3D MA-HA cryogel had a diameter of 5 mm, which is far larger than the diameter of subcutaneous blood vessels, thus minimizing the risk of inadvertent blood vessel embolization.…”
Section: 27mentioning
confidence: 99%
“…Beleznay et al [23] found that the combination of larger volumes of filling material together with a deeper placement of the material increases the risk of vascular compromise. This aspect, coupled with use by physicians who are not experts in the use of these techniques and have an inadequate knowledge of facial anatomy, is leading to an increased risk of complications.…”
Section: Discussionmentioning
confidence: 99%
“…This pivotal role of the facial vein as a hallmark structure in the face is of great importance when trying to understand the detailed anatomy of the facial fat compartments and to avoid complications. Of those, irreversible blindness resulting from filler or autologous fat transfer procedures is considered the most dangerous one [19,27].…”
Section: Discussionmentioning
confidence: 99%